Timber fusion design challenge – uniting design and sustainability / Nur Izzati Afiqah Zaifulashar, Nazrul Helmy Jamaludin and Saifullah Ammar Abdullah - Zaifulashar, Nur Izzati Afiqah; Jamaludin, Nazrul Helmy; Ammar, Saifullah (2024)
Introducing the public space timber fusion. The innovative idea redefines how we view and engage with our urban landscape by fusing the ageless beauty of timber with cutting-edge technology. In a time when aesthetics are valued highly, the Public Space Timber Fusion is a shining example of creativity and originality. Its distinctive fusion of contemporary design ideas with organic materials not only improves public places aesthetics appeal but also fosters a sense of balance and unity to the natural world. With the Public Space Timber Fusion, every park, every plaza and communal area becomes a canvas for architectural excellence. Its versatility allows for the creation of dynamic and inviting spaces that cater to the diverse needs of communities, whether it’s a bustling city square or a tranquil neighbourhood. As we strive to build a more inclusive and environmentally conscious university, the Public Space Timber Fusion emerges as a symbol of progress and possibility. It embodies the fusion of tradition and innovation, offering a glimpse into a future where public spaces are not just functional but inspirational works of art.